2004
DOI: 10.1093/carcin/bgh256
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of p53 mutation analysis in bladder cancer tissue and urine sediment by functional assay in yeast

Abstract: In the present study we correlate the p53 gene mutations in tumour tissue with urine sediment using a functional assay in yeast, and relate the p53 status to the outcome in a group of patients with transitional cell carcinoma of the bladder. The p53 mutations were found in three of 30 (10%) Ta/T1 tumour tissue samples and in two of 20 (10%) corresponding urine sediments. In the stage T2-T4 tumour p53 mutations were found in tumour tissues and urine sediments in 13 of 31 (42%) and in seven of 18 (39%) samples, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Mutant p53 was correlated with positive urine cytology, lymph node involvement, high-stage and high-grade indicating that p53 mutation is a late event in tumor development and is involved in progression of bladder cancer. Our results are consistent with others [8][9][10][11]. In the current study, although the association between mutant p53 and schistosomiasis did Our comparative study indicated that fibronectin had a superior sensitivity (82%) than urine cytology and mutant p53 (59% and 37%, respectively) for detection of bladder cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mutant p53 was correlated with positive urine cytology, lymph node involvement, high-stage and high-grade indicating that p53 mutation is a late event in tumor development and is involved in progression of bladder cancer. Our results are consistent with others [8][9][10][11]. In the current study, although the association between mutant p53 and schistosomiasis did Our comparative study indicated that fibronectin had a superior sensitivity (82%) than urine cytology and mutant p53 (59% and 37%, respectively) for detection of bladder cancer.…”
Section: Discussionsupporting
confidence: 92%
“…The p53 tumor suppressor gene, the central molecule regulating the cell cycle, plays a key role in suppression of neoplastic transformation by cell cycle arrest and/or by apoptosis [6]. Previous reports have shown that p53 mutations can be detected in bladder carcinoma tissue of patients with bladder carcinoma [7][8][9]; however few studies assessed the value of urinary mutant p53 in management of bladder cancer [10,11]. It is noted that all the patients with bladder cancer investigated by Prescott et al [10] and Schlichtholz et al [11] were transitional cell carcinoma (TCC); however, both squamous cell carcinoma (SSC) and TCC exist in Egypt, and schistosomiasis-associated bladder cancer is commonly found.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in defined structural and functional domains of p53 may therefore be useful molecular biological markers for prognosis and treatment strategies of non-invasive transitional cell carcinomas. This finding is even more valuable, since TP53 mutations can be analyzed in urine cells by non-invasive methods (8,39,50). TP53 analyses in tumour tissue or urine cells might guide the clinician towards a more aggressive therapy, such as radical cystectomy for high risk T1G3 or Cis tumours which could otherwise undergo bladder sparing procedures and close surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in defined structural and functional domains of p53 may therefore serve as useful molecular biological markers for determining prognosis and treatment strategies in patients with noninvasive transitional cell carcinomas. This finding is potentially even more significant, because TP53 mutations can be analyzed in urine cells by noninvasive methods (347,348 ). As newer and faster techniques for genetic analysis become available, such testing may become routine in the future.…”
Section: Role Of Urine Markers In Early Detection Of Bladder Cancermentioning
confidence: 99%